EFFICIENCY OF SCAFFOLDING METHOD IN THE LEARNING PROCESS OF MATHEMATICS COMPARATIVE MATERIAL IN GRADE V ELEMENTARY SCHOOL STUDENTS - Saidul, Muhamad Diva; Widyasari, Nurbaiti (Jurnal Pendidikan Matematika (JUPITEK), 2024)
The conceptual understanding of comparative mathematics remains a significant challenge in elementary education, as students rely heavily on formulaic approaches rather than developing deeper comprehension. This condition highlights the importance of the role of teachers in assisting with learning methods such as scaffolding. This study aims to analyze the efficiency of the scaffolding method in improving students' cognitive aspects. Scaffolding can help students improve mathematics learning outcomes and mathematical problem-solving skills and improve the cognitive aspect applied to grade V students in one of the state elementary schools in the Pondok Kacang area. This study uses a descriptive qualitative approach with data collection through observation, interviews, and documentation with data sources of a teacher and 3 grade V students in one of the State Elementary Schools in the Pondok Kacang area. The results of the study on the application of the scaffolding method to improving cognitive aspects in students in the context of learning mathematics ratio materials show that the application of the scaffolding method is efficient and effective; this can be seen from the improvement of students' cognitive aspects through assisting children in the early stages of their development, applying a multi-level approach, and efforts to follow the characteristics of scaffolding when there is an argument between students and teachers. The scaffolding method improves students' cognitive aspects by using motivational strategies and associating students' interests with learning assignments. Therefore, the scaffolding method plays a role in developing students' cognitive skills, especially in mathematics